(untitled) (Journal of Universal Science Research, 2024)
This article explores the basics of infinitives and gerunds, important verb forms in English grammar. Infinitives typically start with "to," while gerunds end in "-ing" and act like nouns. Teaching these concepts involves interactive exercises, role plays, error correction, and real-life examples. By mastering infinitives and gerunds through practical techniques, learners can improve their language skills and communicate more effectively